Karl Adam und der Nationalsozialismus - Scherzberg, Lucia (theologie.geschichte Beihefte, 2022)
During his lifetime, the Tübingen dogmatist Karl Adam was one of the best-known and most influential Catholic theologians in Germany. Later generations saw him as a reformer of Catholic theology and a forerunner of the Second Vatican Council. His deep involvement in National Socialism has long been repressed. Adam was enthusiastic about Adolf Hitler and the new attitude towards life that he felt he felt in the National Socialist "movement". Eventually he became a member of a conspiratorial group of National Socialist priests and ultimately let his theology be determined more by categories such as "people" and "race" than by the Christian message.